(untitled) (Research, Society and Development, 2021)
The present study considers the reality of a mining company called MinerXYZ and the description of the calculation memory for the dimensioning of the rainwater drainage system project. It starts with the drainage project for the Mine called S-1, focusing on the adequate direction of the surface flow along the plateaus and accesses, with the use of drainage devices, to direct them to the decantation basins or safe drain site. The objective of this study was to know the main steps to carry out a rainwater drainage project based on a case study in a mining company. The methodology is descriptive in that it opted for the case study in an iron ore mining company. As a result, it could be verified that the efficiency of the rainwater drainage system for Mine SI proved to be a conclusive result, respecting the appropriate observation period, which underlies the construction of the structural elements of the drainage system for this unit and evaluating its dynamics in the period of greatest rainfall intensity. It was concluded by the importance and necessity of having a drainage system project, considering some necessary resources already existing in Mine SI with an alignment for the elaboration and adequacy of the activity in the enterprise’s routine.